Synergistic Effects of Dantrolene and Nimodipine on the Phenylephrine-Induced Contraction and ACh-Induced Relaxation in Aortic Rings from Diabetic Rats. (19th April 2018) - Crespo, Maria J.; Roman, Marie; Matias, Jonathan; Morales, Myrna; Torres, Hector; Quidgley, Jose
Abstract : Diabetics have a higher risk of developing cerebral vasospasms (CVSP) than nondiabetics. The addition of the ryanodine receptor (RyR) blocker dantrolene to standard therapies reduces vasospasms in nondiabetics. Whether diabetics with CVSP also benefit from this drug, however, is unknown. We evaluated the effects of a 30 min incubation with dantrolene (50  μ M), nimodipine (50 nM), and both drugs in combination, on phenylephrine- (PHE-) induced contraction and on acetylcholine- (ACh-) induced relaxation in aortic rings from streptozotocin (STZ) diabetic rats. Age-matched, nondiabetic rats served as controls. The oxidative stress markers malondialdehyde (MDA) and 4-hydroxyalkenal (4-HAE) were also evaluated in the presence and absence of dantrolene and nimodipine. The combination of these two drugs acted synergistically to reduce the PHE-induced contraction by 80% in both diabetics and controls. In contrast, it increased theE max value for ACh-induced relaxation (from 56.46 ± 5.14% to 96.21 ± 7.50%;n = 6, P < 0.05 ), and it decreased MDA + 4-HAE values in diabetic rats only. These results suggest that the combination of dantrolene and nimodipine benefits both diabetics and nondiabetics by decreasing arterial tone synergistically.